Penguasaan Konsonan Aspirasi Bahasa Korea Pemelajar Orang Indonesia - Meutia, Fitri; Faisal, Rahmad; Dessiar, Achmad Rio; Lubis, Arif Husein; Adnyana, Putu Pramania; Hilma, Ananda Adella; Ningrum, Tantri Pramudita (JLA (Jurnal Lingua Applicata), 2025)
This research aims to determine the understanding ability of aspirated consonants ㅋ (kh), ㅌ (th), ㅍ (ph) of second and third-year Korean language students and whether there are significant differences between each group of participants. The participants in this study included 20 second-year and 20 third-year Korean language students at National University, as well as 20 comparison groups of native Korean speakers. To determine the understanding of these groups, a listening test known as the identification test was administered. The test consisted of 10 sentences in which each sentence contained a word containing the Korean aspirated letters ㅋ (kh), ㅌ (th), and ㅍ (ph). From the results of this test, the average score of native Korean speakers obtained a score of 98, second-year students obtained an average score of 43, and third-year students obtained an average score of 38.5. Then, to find out whether there is a difference between each group, especially the native speakers and Korean language students,  ANOVA statistical test was conducted, the test results found that there was a highly significant difference between native Korean speakers and second-year students with a significance value of 0.00 (sig < 0.05), native Korean speakers and third-year students with a significance value of 0.00 (sig < 0.05), and there was no difference between second-year and third-year students with a significance value of 0.612 (sig > 0.05). This means that native speakers of Korean have high consonant understanding, while second and third year students have very low aspirated consonant understanding ability.